Diseño de paquetes turísticos en época de la COVID-19 para los ciudadanos del cantón Buena Fe, provincia de Los Ríos, año 2021 - Ponce Bravo, Nathaly Yamilet (2021)
This research project was carried out in Buena Fe canton, Los Ríos province to design tourist packages for citizens in the time of COVID-19 as a contribution to the country’s tourist reactivation from the strengthening of internal tourism, also for the benefit of the community for the economic income that would be generated with the exercise of the activity. For the development of the project four objectives were raised that were fulfilled through a documentary, field and descriptive research, the reopened tourist sites in the canton were identified and inventory through the survey and ranking sheets of tourist attractions obtaining information through field visits and direct observation. Surveys were carried out on 379 people considered the study population to determine the profile of the tourist at the time of COVID-19 where it was found that 53,03% fully agree and 31,66% agree that tourist packages of the locality are designed and promoted, evidencing a high degree of acceptance of the aforementioned proposal. For the design of tourist packages the profile of the tourist was taken into account elaborating 3 packages adjusted to their new needs: “Adventuring in the friendliest city in Ecuador, Buena Fe”, “Buena Fe, enchanted paradise” and “Discovering natural riches of Buena Fe” where the activities to be carried out in the itinerary, the services, prices and attractions that are included in the package were detailed, for the promotion of them tourist infographics were elaborated to motivate and encourage tourists to visit these spaces in times of pandemic with biosecurity measures, increasing the arrival of visitors and in turn improving the quality of life of the town. Key words: tourist attractions, tourist packages, internal tourism, tourist reactivation. X